2019
DOI: 10.1021/acs.est.8b05825
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Pyrolytic Remediation of Crude-Oil-Contaminated Soil in a Continuously-Fed Reactor: Treatment Intensity Trade-Offs

Abstract: Pyrolytic treatment offers the potential for the rapid remediation of contaminated soils. However, soil fertility restoration can be highly variable, underscoring the need to understand how treatment conditions affect soil detoxification and the ability to support plant growth. We report here the first pilot-scale study of pyrolytic remediation of crude-oil-contaminated soil using a continuously fed rotary kiln reactor. Treatment at 420 °C with only 15 min of residence time resulted in high removal efficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Cell viability assays revealed that pyrolytic treatment effectively detoxified the contaminated soil, indicating that pyrolysis does not have the residual toxicity drawback of some aerobic bioremediation methods. 12 At the same time, this study 24 revealed an interesting tradeoff. While TPH and PAH removal levels improved with increasing treatment intensity 25 (i.e., higher temperatures and longer reactor residence times), the fertility of treated soil first improved and then declined when the treatment intensity exceeded a soil-specific threshold.…”
Section: ■ Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Cell viability assays revealed that pyrolytic treatment effectively detoxified the contaminated soil, indicating that pyrolysis does not have the residual toxicity drawback of some aerobic bioremediation methods. 12 At the same time, this study 24 revealed an interesting tradeoff. While TPH and PAH removal levels improved with increasing treatment intensity 25 (i.e., higher temperatures and longer reactor residence times), the fertility of treated soil first improved and then declined when the treatment intensity exceeded a soil-specific threshold.…”
Section: ■ Introductionmentioning
confidence: 60%
“…In a recently published article, we reported results from the first pilot-scale study of pyrolytic soil treatment performed in a continuous rotating kiln reactor. 24 Pyrolysis at 420 °C with 15 min residence time achieved almost complete TPH removal (99.9%), removed almost 95% of the PAHs present in the contaminated soil, and restored the fertility of treated soil to almost clean soil levels. Cell viability assays revealed that pyrolytic treatment effectively detoxified the contaminated soil, indicating that pyrolysis does not have the residual toxicity drawback of some aerobic bioremediation methods.…”
Section: ■ Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hydrocarbons will generate free radicals due to thermal activation at around 400°C, and a series of free radical reactions will occur. On the one hand, it will proceed towards the cracking of small-molecule hydrocarbons while it proceed towards the condensation direction of coking and finally produce oil, water, noncondensable gas, and coke [ 19 ]. In comparison, the pyrolysis method has the advantages of faster processing speed, more thorough oily sludge treatment, and recyclable oil and gas and residues.…”
Section: Research Progress Of Catalytic Pyrolysis Of Oily Sludgementioning
confidence: 99%